Recent Cases in International Investment Law Involving Local Government on Investment Disputes - Oktaviandra, Surya (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2023)
An understanding of the importance of regulating investment treaties and implementing measures in accordance with existing rules has been generally understood by States in foreign direct investment. However, the local government where the location of foreign investment activities is carried out has not received sufficient attention. As a result, various cases of international investment disputes have arisen caused by actions taken by local governments. This study discusses how the tribunal views and interprets actions taken by local governments in relation to violations of foreign investor rights. In the span of time over the past eight years, no less than six hundred cases of foreign investment disputes have been investigated. Of these, three available and final cases became the subject of discussion in research and became examples to link them with the legal skills of local government officials in mitigating the occurrence of foreign investment case disputes. The results of this study show that in terms of understanding the rules of international investment law, the government in the country can mitigate or handle the case better with foreign investment disputes.